Media Pembelajaran Multimedia Interaktif Menggunakan Metode MDLC Pada Zoom Meetings - Aji Wardana; Muhammad Rizky Ramadhan; Mahzura Aznur; Rizka Annisa Putri; Ali Ikhwan (LPPM Universitas Dharma Andalas, 2023)
Multimedia is a means of disseminating information so that multimedia can be used as an interactive learning medium. This research is based on the results of previously written studies which aim to create a learning media from the discussion results of previous people. Data collection uses the MDLC (Multimedia Development Life Circle) method. The results of this research are to successfully create interactive multimedia learning media using the MDLC (Multimedia Development Life Circle) method as an interactive learning media facility using Zoom Meeting as the meeting medium. This learning media has been tested. Tests in research use tests that focus on the results of visualization displays and effectiveness in conveying information.